National Policies and the Role of English in Higher Education - Liu, Xinyan (International Higher Education, 2018)
Past research and debate on the use of English in higher education has mostly focused on northern European countries, as they were among the first to consider using English as a language of instruction. This paper seeks to broaden the topic by focusing on a diverse group of countries including Brazil, France, Malaysia, South Africa, and Spain. The two key aspects discussed here concern existing national policies regarding language in higher education in the target countries and the role of English in their respective higher education systems.